Phosphoglycerate mutase 5 exacerbates cardiac ischemia-reperfusion injury through disrupting mitochondrial quality control - Zhu, Hang (Redox Biol, 2020)
The death of cardiomyocytes either through apoptosis or necroptosis is the pathological feature of cardiac ischemia-reperfusion (I/R) injury. Phosphoglycerate mutase 5 (PGAM5), a mitochondrially-localized serine/threonine-protein phosphatase, functions as a novel inducer of necroptosis. However, intense debate exists regarding the effect of PGAM5 on I/R-related cardiomyocyte death. Using cardiac-specific PGAM5 knockout (PGAM5(CKO)) mice, we comprehensively investigated the precise contribution and molecular mechanism of PGAM5 in cardiomyocyte death. Our data showed that both PGAM5 transcription and expression were upregulated in reperfused myocardium. Genetic ablation of PGAM5 suppressed I/R-mediated necroptosis but failed to prevent apoptosis activation, a result that went along with improved heart function and decreased inflammation response. Regardless of PGAM5 status, mitophagy-related cell death was not apparent following I/R. Under physiological conditions, PGAM5 overexpression in primary cardiomyocytes was sufficient to induce cardiomyocyte necroptosis rather than apoptosis. At the sub-cellular levels, PGAM5 deficiency increased mitochondrial DNA copy number and transcript levels, normalized mitochondrial respiration, repressed mitochondrial ROS production, and prevented abnormal mPTP opening upon I/R. Molecular investigation demonstrated that PGAM5 deletion interrupted I/R-mediated Drp(S637) dephosphorylation but failed to abolish I/R-induce Drp1(S616) phosphorylation, resulting in partial inhibition of mitochondrial fission. In addition, declining Mfn2 and OPA1 levels were restored in PGAM5(CKO) cardiomyocytes following I/R. Nevertheless, PGAM5 depletion did not rescue suppressed mitophagy upon I/R injury. In conclusion, our results provide an insight into the specific role and working mechanism of PGAM5 in driving cardiomyocyte necroptosis through imposing mitochondrial quality control in cardiac I/R injury.